2014
DOI: 10.4269/ajtmh.13-0475
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Evaluation of the Efficacy of Soapy Water to Clean Hands: A Randomized, Non-Inferiority Field Trial

Abstract: Abstract. We conducted a randomized, non-inferiority field trial in urban Dhaka, Bangladesh among mothers to compare microbial efficacy of soapy water (30 g powdered detergent in 1.5 L water) with bar soap and water alone. Fieldworkers collected hand rinse samples before and after the following washing regimens: scrubbing with soapy water for 15 and 30 seconds; scrubbing with bar soap for 15 and 30 seconds; and scrubbing with water alone for 15 seconds. Soapy water and bar soap removed thermotolerant coliforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 38 publications
2
71
0
Order By: Relevance
“…6,7 To address the barrier of soap cost, handwashing with soapy water (detergent powder plus water) could be promoted. Soapy water is just as microbiologically effective as bar soap at reducing fecal indicator organisms from hands, 35 and it is acceptable elsewhere in Bangladesh. 36 A trial of individual and combined water, sanitation, hygiene, and nutrition interventions (WASH Benefits; www.washbenefits.org) will likely provide insights on the health benefit of washing hands with soapy water.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 To address the barrier of soap cost, handwashing with soapy water (detergent powder plus water) could be promoted. Soapy water is just as microbiologically effective as bar soap at reducing fecal indicator organisms from hands, 35 and it is acceptable elsewhere in Bangladesh. 36 A trial of individual and combined water, sanitation, hygiene, and nutrition interventions (WASH Benefits; www.washbenefits.org) will likely provide insights on the health benefit of washing hands with soapy water.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly this study, 3% used protected dug wells which is less than by 13% revealed in study conducted (16% used protected dug well) on microbiological evaluation of the efficacy of soapy water to clean hands in 2014 [18]. This may be due to geographic, lack of awareness toward use of improved water sources and lack of access improved water supply sources.…”
Section: Discussionmentioning
confidence: 81%
“…In Ethiopia, only 16% (piped and a protected well) and 12% of a protected spring were in rural households [18] and 53% households travel 30 minutes or more to fetch their drinking water (19% in urban and 62% rural areas) [19]. The study on access to safe drinking water and availability of environmental sanitation facilities among Dukem town households in 2013 pointed that almost all the households had access to improved water supply and quite large of them are unimproved toilet facility [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of handwashing or handscrubbing was not considered, because growing evidence suggests that it is less relevant for handwashing effectiveness. [31][32][33] Thoroughness of …”
Section: Introductionmentioning
confidence: 99%